2008
DOI: 10.1053/j.ajkd.2008.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Versus Oral Iron Supplementation for the Treatment of Anemia in CKD: Systematic Review and Meta-analysis

Abstract: Our review shows that patients on hemodialysis therapy have better Hb level response when treated with IV iron. For patients with CKD, this effect is small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(135 citation statements)
references
References 35 publications
4
121
0
10
Order By: Relevance
“…This study is consistent with other studies that showed that in iron deficient hemodialysis patients randomized to oral iron or intravenous iron, only the group treated with intravenous iron had a significant increase in hemoglobin levels [9][10][11][12]. Intravenous iron preparations have very different molecular weights and side effect profiles [13], small proportions of patients given intravenous iron dextran develop a lifethreatening anaphylactic reaction, which is due to an immune-mediated reaction in patients who have dextran antibodies [14].…”
Section: Discussionsupporting
confidence: 90%
“…This study is consistent with other studies that showed that in iron deficient hemodialysis patients randomized to oral iron or intravenous iron, only the group treated with intravenous iron had a significant increase in hemoglobin levels [9][10][11][12]. Intravenous iron preparations have very different molecular weights and side effect profiles [13], small proportions of patients given intravenous iron dextran develop a lifethreatening anaphylactic reaction, which is due to an immune-mediated reaction in patients who have dextran antibodies [14].…”
Section: Discussionsupporting
confidence: 90%
“…previous studies have reported that patients undergoing hd showed a better response to iV iron; however, patients with crF showed no difference between oral and iV iron (9). another study demonstrated that iV and oral iron caused a similar correction in anemia over 6 weeks (17).…”
Section: Discussionmentioning
confidence: 86%
“…a recent systemic review and meta-analysis suggested that patients treated with iV iron have better hemoglobin (hb) levels than those treated with oral iron (9). however, some studies have found that oral iron is well tolerated and effective in long-term hd patients (10) and as effective as iV iron in pre-dialysis patients (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…iron can augment the response to erythropoietin therapy and significantly impact the dose requirements of erythropoietin in dialysis patients. The situation in nondialysis patients is less clear cut [36]. Many units, particularly in the early stages of CKD, try oral iron supplementation first, reserving i.v.…”
Section: Experience With IV Iron In Nephrologymentioning
confidence: 99%